INFLUENCE OF SUPPLY BASE RATIONALIZATION ON PERFORMANCE OF MANUFACTURING FIRMS IN KENYA - CHEGE, ANTONY NYUTU; OCHIRI, Dr, GEORGE (International Journal of Supply Chain and Logistics, 2019)
Purpose: The study aimed at establishing how; triangle approach, Pareto's approach, "˜improve or else' method and competency staircase method influence the performance of manufacturing firms in Kenya. Methodology: The study employed a descriptive research design, the study prefers this method because it allows an in-depth study of the subject. The 2017 KAM directory has listing of members (firms) by sectors which contains a register of 12 sectors of those in manufacturing firms spread all over the country. The population of the large sized registered members as per the directory is 499.This study used the large sized firms only. This study used Cochran's formula to sample 165 large manufacturing firms from the total population, heads of procurement were the respondents. Semi-structured questionnaires were administered to collect qualitative and quantitative data. Secondary data was collected from firm's reports and websites. Results: The findings of the study indicated that triangle approach, Pareto's approach, improve or else method and competency staircase method have a positive relationship with performance of manufacturing firms in Kenya. Conclusion: Based on the study findings, the study concludes that performance of manufacturing firms can be improved by triangle approach, Pareto's approach, improve or else method and competency staircase method. Policy recommendation: The study recommended that manufacturing firms should embrace supply base rationalization so as to improve performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.